Agricultural Waste Based-Coco Peat Microwave Absorber - Seok, Yew Been; Fwen Hoon, Wee (2014)
This paper presents the performance of coco peat microwave absorber in terms of dielectric properties and reflection loss. Coco peat microwave absorber was fabricated using raw coco peat, polyester resin and MEKP hardener. The dielectric properties and reflection loss of coco peat microwave absorber is measured using Agilent E8362B P-series Network Analyzer. Dielectric properties of coco peat microwave absorber were determined by open-ended method via coaxial probe while the reflection loss of coco peat microwave were determined by waveguide method via WR-90 waveguide adapters over X band frequency (8 GHz- 12.4 GHz). Coco peat microwave absorber achieved desirable reflection loss below -30dB which indicates that more than 90 % of microwave absorbing efficiency. It is potentially useful as a substitute material for microwave absorber.